2010
DOI: 10.1073/pnas.1003009107
|View full text |Cite
|
Sign up to set email alerts
|

Extra-large pore zeolite (ITQ-40) with the lowest framework density containing double four- and double three-rings

Abstract: The first zeolite structure (ITQ-40) that contains double four (D4) and double three (D3) member ring secondary building units has been synthesized by introducing Ge and NH 4 F and working in concentrated synthesis gels. It is the first time that D3-Rs have been observed in a zeolite structure. As was previously analyzed [Brunner GO, Meier, WM (1989) Nature 337:146-147], such a structure has a very low framework density (10.1 T∕1,000 Å 3 ). Indeed, ITQ-40 has the lowest framework density ever achieved in oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 45 publications
2
132
0
4
Order By: Relevance
“…184,185,186 Moreover, it was demonstrated that germanium very preferentially occupies D4R positions. 187,188,189,190 One of these structures was ITQ-15, 191 which structure was shown to be formed by 14x12 ring pores and was denominated UTL, following the IZA code (see Figure 28a).…”
Section: -Synthesis Of Layered Structures From Germanosilicatesmentioning
confidence: 99%
“…184,185,186 Moreover, it was demonstrated that germanium very preferentially occupies D4R positions. 187,188,189,190 One of these structures was ITQ-15, 191 which structure was shown to be formed by 14x12 ring pores and was denominated UTL, following the IZA code (see Figure 28a).…”
Section: -Synthesis Of Layered Structures From Germanosilicatesmentioning
confidence: 99%
“…While several intriguing zeolites with densities in this range have recently been synthesized, 15,16 …”
Section: Density and Energy Distributionmentioning
confidence: 99%
“…In fact, zeolites with 16-ring pores are very rare; the only example is the germanosilicate ITQ-40 (22). ITQ-51 is one of the very few extra-large-pore zeolites with ≥16-ring channels that are stable in air after calcination.…”
Section: Resultsmentioning
confidence: 99%
“…Although Curtis and Deem (19) predicted that these zeolitic structures are thermodynamically feasible, only three microporous materials with 16-rings have been reported. Of these three materials, two are oxyfluorinated gallium phosphates, ULM-5 (20) and , with gallium in diverse atomic coordination (tetrahedral and octahedral); the other is the germanium-rich ITQ-40 containing 16 × 16 × 15-rings and structural defects (22). More specifically, in the AlPO family, it is possible to find structures with 12-, 14-, and 18-rings, but AlPO structures with 16-rings have not been reported up to now, as far as we know.…”
mentioning
confidence: 99%